Effects of water deficit and pH on seed germination and seedling development in Cereus jamacaru - Thiago Alberto Ortiz; Mariana Ragassi Urbano; Lúcia Sadayo Assari Takahashi (Semina: Ciências Agrárias, 2019)
The lack of water and soil acidity are current problems occurring in many regions around the globe. Therefore, it is essential to investigate the effects of seed germination and seedling development, in order to determine the species adaptability to the ever-changing environment. The aim of this study was to evaluate the effects of water deficit and pH on seed germination and seedling development in Cereus jamacaru. A completely randomized experiment was performed. A factorial scheme of 6 × 7, corresponding to six osmotic potential values (0.0, -0.2, -0.4, -0.6, -0.8, and -1.0 MPa) induced by PEG 6000, and seven pH levels (3, 4, 5, 6, 7, 8, and 9) with four replications was used. The variables analyzed were germination (G), germination speed index (GSI), mean germination time (MGT), normal seedling (NS), root length (RL), shoot length (ShL), seedling length (SL), and seedling dry mass (SDM). The statistical analysis included ANOVA and binomial models (G and NS), regression models with quadratic terms (GSI and MGT), and response surface method (ShL and SL) for the variables with at least one significant factor (p < 0.05). C. jamacaru showed susceptibility to water deficit at seed germination and seedling development stages, indicated by the decreases in G, GSI, NS, ShL, and SL at osmotic potential below to 0.0 MPa. The pH interaction with osmotic potential affected C. jamacaru seedling development. The increase in pH was favorable for seedling development, but not for seed germination.